2020
DOI: 10.1186/s40792-020-00861-6
|View full text |Cite
|
Sign up to set email alerts
|

Port site recurrence of esophageal adenocarcinoma after minimally invasive esophagectomy: a case report

Abstract: Background: Port site recurrence has been observed after a variety of oncologic resection procedures. However, few have reported port site recurrence of esophageal cancer. Case presentation: A 51-year-old man underwent minimally invasive esophagectomy for pT3(AD)N3M0 adenocarcinoma of the esophagus. One year after surgery, he presented with a rapidly growing tumor on the right thoracic wall. Contrast computed tomography demonstrated an enhancing tumor with uptake on positron emission tomography. We performed r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…Our case demonstrates a rare presentation of EAC with metastasis to the chest wall that adds to the few reported cases in the literature [ 3 - 4 , 7 - 10 ]. While EAC commonly metastasizes to the liver and lungs, there are other locations to which it only rarely metastasizes, such as the subcutaneous region.…”
Section: Discussionsupporting
confidence: 58%
“…Our case demonstrates a rare presentation of EAC with metastasis to the chest wall that adds to the few reported cases in the literature [ 3 - 4 , 7 - 10 ]. While EAC commonly metastasizes to the liver and lungs, there are other locations to which it only rarely metastasizes, such as the subcutaneous region.…”
Section: Discussionsupporting
confidence: 58%
“…According to previous reports, the main therapeutic strategy of PSR may be chemotherapy, radiotherapy, or surgical resection [ 23 , 24 ]. Several reports have described successful local resection of PSR that had occurred without peritoneal dissemination and/or distant metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have described successful local resection of PSR that had occurred without peritoneal dissemination and/or distant metastasis. These patients achieved long-term survival after PSR resection [ 4 , 23 , 26 ]. Wang et al [ 27 ] suggested that surgical resection is an effective treatment for PSR without another peritoneal dissemination.…”
Section: Discussionmentioning
confidence: 99%